The Equivalence of the Liquidity Preference and Loanable Funds Theories and the New Stock-Flow Analysis - Lloyd, Cliff L. (Review of Economic Studies, 1960)
The Equivalence of the Liquidity Preference and Loanable Funds Theories and the New Stock-Flow Analysis Get access Cliff L. Lloyd Cliff L. Lloyd Khartoum Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 3, June 1960, Pages 206–209, https://doi.org/10.2307/2296083 Published: 01 June 1960